2020
DOI: 10.1021/acsomega.0c04191
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Decorated Cobalt Ferrite Nanoparticles Anchored onto the Graphene Sheets as Electrode Materials for Electrochemical and Photocatalytic Applications

Abstract: The present work describes the synthesis of Ag-CoFe2O4/rGO nanocomposite as a photocatalyst through the hydrothermal process by the attachment of silver and cobalt ferrite (CoFe2O4) nanoparticles on the surface of reduced graphene oxide. The effect of Ag and reduced graphene oxide (rGO) on the structure, optical, magnetic, photocatalytic, and electrochemical performance of the CoFe2O4 is systematically explored through various analytical techniques. The analyses of the observed outcomes reveal that the graphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Further, Figure c depicts a representative TEM image of the CZ2 sample, which signifies spherical nanoparticles with sizes in the range of 5–9 nm. The periodic lattice fringe spacing of 0.29 nm corresponding to the (220) plane of the spinel ferrite structure can be noticed in Figure d …”
Section: Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Further, Figure c depicts a representative TEM image of the CZ2 sample, which signifies spherical nanoparticles with sizes in the range of 5–9 nm. The periodic lattice fringe spacing of 0.29 nm corresponding to the (220) plane of the spinel ferrite structure can be noticed in Figure d …”
Section: Results and Discussionmentioning
confidence: 95%
“…The periodic lattice fringe spacing of 0.29 nm corresponding to the (220) plane of the spinel ferrite structure can be noticed in Figure 4d. 60 Furthermore, a typical TEM image of the CZ3 sample is shown in Figure 4e, which represents spherical nanoparticles with sizes in the range of 3−6 nm. The distinct lattice fringes with a spacing of 0.25 nm corresponding to the (311) planes of cubic spinel ferrite can be observed in Figure 4f.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of C=O and C-O at the 1713.96 and 1048.37 cm −1 bands indicate the reduction of GO into rGO [ 46 ]. Moreover, O-H stretching vibrations were observed at 3433.69, 1646.43, and 1353 cm −1 for both SnO 2 NPs and SnO 2 -rGO NCs due to the existence water molecules during the hydrothermal process [ 47 ]. The band observed at 593 cm −1 was assigned to the O-Sn-O stretching mode in the SnO 2 NPs [ 48 ], while two strong peaks at 530.20 and 608.6 cm −1 in the SnO2-rGO NCs were assigned to Sn-O stretching vibration owing to the strong interaction between SnO2 and rGO [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Improvements in photocatalytic pollutant removal efficiency arising from silver integration onto magnetic materials are also evident in the case of pharmaceutical pollutants such as tetracycline [69] and sulfanilamide [70]. The silver addition has been proven to enhance the photocatalytic degradation and antibacterial action, not only under UV but under visible illumination as well [10,20,46,62,66,68], even when the base materials are not especially effective under these conditions [20]. In summary, the combined attributes of magnetic materials and silver lead to significantly enhanced composites with usage flexibility.…”
Section: Magnetic Materials and Silver Enhancementmentioning
confidence: 99%
“…In a recent work, Ibrahim et al (2022) observed significantly enhanced photocatalytic pollutant removal efficiency after silver integration for their best TiO 2 /g-C 3 N 4 /Ag sample in both oxidation (azo-dyes/pharmaceuticals) and reduction (Cr 6+ and 4-nitrophenol) processes [61]. Composites with magnetic materials and silver have been proven to be especially efficient in the treatment of heavy metal pollutants, such as Cr 6+ [20] or organics such as methylene blue [10,62,63], rhodamine B [10,46,64,65], malachite green [63,66] and phenol [63,67], along with the photocatalytic neutralization of bacteria such as Escherichia coli [63,68] and Micrococcus luteus [63]. Improvements in photocatalytic pollutant removal efficiency arising from silver integration onto magnetic materials are also evident in the case of pharmaceutical pollutants such as tetracycline [69] and sulfanilamide [70].…”
Section: Magnetic Materials and Silver Enhancementmentioning
confidence: 99%